Um percurso vivido: pluralizando histórias e memórias a partir do projeto “Territórios Negros” - Francieli Renata Ruppenthal (Ciências Sociais Unisinos)
This article is based on the reflection made in my masters’ thesis, which dealt with the pro-ject “Territórios Negros: Afro-Brasileiros em Porto Alegre” (Black Territories: Afro-Brazilians in Porto Alegre). The project “Black Territories”, whose objective is to help implementing Federal Law 10.639/03, consists in a bus that drives through central areas in Porto Alegre aiming to show students the so called “black territories”. Through the direct observation of the journeys, ethnographically, this article presents some perceptions, narratives, stories and memories of the participants and the team that worked in the project, based on the theoretical reflection by authors such as Jardim (2013), Chagas (2005), Leite (1991) and Rolnik (1989). By going through each and every point and emphasizing the multiple voices that bring the journey to life and give purpose to the black territories, it is possible to notice reflections on several questions that involve the themes of race and ethnicity, such as racism. The article concludes that the effects produced by the project surpassed the creators’ expectations.